Small Molecule SPR Imaging Detection from Split Aptamer Microarrays. (2017) - Melaine, Feriel; Roupioz, Yoann; Buhot, Arnaud
Abstract: The small molecules detection remains a challenge for diagnostics. Due to their size, difficulties arise in finding selective and sensitive probes as well as developing appropriate detection format based on sandwich and/or signal amplification assays. In this study, we combine multiple strategies: a) the use of aptamer probes, short oligonucleotides strands selected in order to present strong selectivity for the small molecule target, b) the sequence engineering of split versions of the aptamer for a sandwich assay and c) the amplification of Surface Plasmon Resonance imaging (SPRi) signal by the use of gold nanoparticles (AuNPs). Combining those three strategies lead to state-of-the-art limit of detection (LOD = 50 nM) for the adenosine target.